Pola Komunikasi pada Sekolah Biruku Indonesia - Diva Salwa; Doddy Iskandar C (UNISBA Press, 2024)
Abstract. Communication is an important thing that will always exist in human life. The communication process in learning activities is very important because it can be one of the factors in increasing student achievement. The development of relationships between teachers and students can be viewed from personal experiences of interpersonal communication of teachers and students using social penetration theory. Social penetration theory is a meaningful theory as one of the models that show the development of relationships, as the process of individuals getting to know each other through the stage of information disclosure This study aims to determine how communication patterns are applied by teachers to students with Down syndrome at Biruku Indonesia school. The research method used is a qualitative method with a case study approach. Researchers conduct data collection techniques through in-depth interviews, observations, and literature studies. The results of this research show that the form of communication patterns applied by teachers to Down syndrome students at the Biruku Indonesia School is carried out directly and face to face or can also be called interpersonal communication. Apart from interpersonal communication, Biruku Indonesia school teachers use verbal and non-verbal communication according to the characteristics of each student. This is demonstrated by the results of interviews which show that students understand the communication carried out by their teachers in accordance with the special method provided by implementing a system of teacher observation of students, providing temporary material for 3 months to see progress, and permanent material for students' cognitive development. Abstrak. Komunikasi merupakan satu hal penting yang akan selalu ada dalam kehidupan manusia. Proses komunikasi dalam kegiatan pembelajaran sangatlah penting karena dapat menjadi salah satu faktor dalam meningkatkan prestasi siswa. Pengembangan hubungan antara guru dengan murid dapat ditinjau dari pengalaman pribadi komunikasi interpersonal guru maupun murid dengan menggunakan teori penetrasi sosial. Teori penetrasi sosial merupakan teori yang bermakna sebagai salah satu model yang menunjukkan perkembangan hubungan, sebagai proses individu saling mengenal satu sama lain melalui tahap pengungkapan informasi Penelitian ini bertujuan untuk mengetahui bagaimana pola komunikasi yang diterapkan oleh guru pada murid dengan kelainan down syndrome pada sekolah Biruku Indonesia. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan studi kasus. Peneliti melakukan teknik pengumpulan data melalui wawancara mendalam (in depth interview), observasi, dan studi pustaka. Hasil penelitinian ini menunjukan jika bentuk pola komunikasi yang diterapkan oleh guru kepada siswa down syndrome di Sekolah Biruku Indonesia dilakukan secara langsung dan bertatapan muka atau dapat disebut juga komunikasi interpersonal. Selain komunikasi interpersonal, guru sekolah Biruku Indonesia memakai komunikasi verbal dan non-verbal menyesuaikan karakteristik masing-masing siswanya. Hal ini ditunjukan dari hasil wawancara yang menunjukan bahwa siswa memahami komunikasi yang dilakukan gurunya sesuai dengan metode khusus yang di berikan dengan menerapkan sistem observasi guru terhadap siswa, pemberian materi sementara selama 3 bulan untuk melihat perkembangan, dan materi tetap untuk perkembangan kognitif siswa.